Nanopartículas de dextrana enxertada com poli(N-isopropilacrilamida) via reação de formação de base de Schiff para terapia combinada contra o câncer - Carneiro, Maria José Magalhães (2023)
Chemotherapy is one of the main therapeutic modalities against cancer, with doxorubicin (DOX) being one of the most effective drugs in the treatment of various types of neoplasms. However, due to the complexity and resistance of the disease, the effectiveness of monotherapy is generally limited. Studies have shown that the combination of chemotherapy and photodynamic therapy (PDT) can improve the effectiveness of treatments, making it a promising strategy for cancer therapy. Curcumin (CUR), a compound extracted from the rhizomes of Curcuma longa, possesses photosensitizing properties, enabling its use in PDT. Stimuli-responsive nanoparticles are gaining prominence in the delivery of therapeutic agents, mainly because they can promote selective release in tumor environments and thus minimize side effects. In this study, copolymers of dextran grafted with poly(N-isopropylacrylamide) (PNIPAM) were synthesized via Schiff base formation reaction, obtaining nanoparticles co-incorporated with DOX and CUR for use in PDT combined with chemotherapy. Dynamic light scattering analysis showed that the copolymers are thermo- and pH-responsive. DOX was conjugated to the copolymers via Schiff base formation, resulting in nanoparticles smaller than 130 nm, and CUR was co-incorporated through non-covalent interaction, yielding nanoparticles smaller than 90 nm. The release profiles of nanoparticles loaded with DOX and DOX/CUR were pH-dependent, with a higher percentage of DOX and CUR released at pH 5.0. The nanoparticles provided protection for CUR against degradation processes. In vitro cytotoxicity assays demonstrated that nanoparticles loaded with DOX and DOX/CUR inhibit the proliferation of human colorectal cancer cells (HCT-116) and lead to reduced cytotoxicity in non-tumor murine fibroblast cells (L929). With PDT, nanoparticles loaded with DOX/CUR caused higher cytotoxicity compared to nanoparticles incorporated only with DOX. Therefore, nanoparticles loaded with DOX/CUR are promising for selective co-delivery of drugs into cancer cells and have potential applications in combination therapy against cancer.